how do you solve 3x-4<6x-19


Notice: Undefined variable: position6 in /home/domains2/public_html/painphr.com/show.php on line 143

Guide :

how do you solve 3x-4<6x-19

Solve the inequality for  . Simplify your answer as much as possible.

Research, Knowledge and Information :



Notice: Undefined variable: go_page in /home/domains2/public_html/painphr.com/show.php on line 211

2 [5x-(3x-4)] &lt; 3 (2x+3) - Brainly.com


2 [5x-(3x-4)] < 3 (2x+3 ... If you would like to solve the inequation 2 * [5x - (3x - 4)] < 3 * (2x + 3), you can do this using ... [2x + 4] < 6x + 9 2 * 2x + 2 * 4 ...
Read More At : brainly.com...

6x-4 &lt; -34 or 3x+10&gt;10 - Brainly.com


6x-4 < -34 or 3x+10>10 - 1788181. 1. Log in ... 6x-4 < -34 or 3x+10>10 1. Ask for details ; Follow; ... still 0. x > 3 What are you asking here? To solve the equations?
Read More At : brainly.com...

How Do You Simplify 2x / X^2-3x-10 3 - prijom.com


How Do You Simplify 2x / X^2-3x-10 3. ... 3x &lt 7+3. You can simplify 7+3 without affecting the inequality: ... T 5/3). 5. (3x + 1)(7x 2) (3x + 4)(6x 1) x(2x 19). 6 ...
Read More At : prijom.com...

choose the correct solution and graph for the inequality. 3y ...


choose the correct solution and graph for the inequality. 3y-4&lt;-19 or ... how do you solve an ... Graph the linear equation y= 3x + 3 A B ... Algebra How do you ...
Read More At : www.jiskha.com...

Solve Linear Inequalities - Tutorial


Solve Linear Inequalities - Tutorial. Solve linear inequalities: ... 6x + 4 -20 > 8x - 24 6x - 16 > 8x ... Example 4: Solve the inequality
Read More At : www.analyzemath.com...

MO bisects &lt;LMN,m&lt;NMO=(6x+19) ,andm&lt;LMO=(9x-14 ...


MO bisects &lt;LMN,m&lt;NMO=(6x+19) ,andm&lt;LMO=(9x ... i know you go x/2+3x+1. but how do i solve that?? b) (f-g)(x) i know you go x/2-3x+1, how do i solve? c)(f*g ...
Read More At : www.jiskha.com...

solving 12x^3 - 16x^2 + 7x - 1 = 0; solve 3x/(x^2 - 4) < -1


... 16x^2 + 7x - 1 = 0; solve 3x/(x^2 - 4) ... [tex]\text{Then we factor the cubic: }\:12x^3 - 16x^2 + 7x - 1 \;=\;(2x-1)(6x^2 - 5x + 1) \;=\;(2x-1)(2x-1)(3x-1)[/tex ...
Read More At : www.freemathhelp.com...

algebra precalculus - How do you solve for x in this equation ...


... this equation write $$x^3+4x^2+6x=a-4$$ you could solve using ... will be positive if $a \gt 4$, $0$ if $x=4$ and negative if $a \lt 4$. ... How do you solve for ...
Read More At : math.stackexchange.com...

Suggested Questions And Answer :



Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

How do I solve y=-x-4

How do I solve y=-x-4 I need to be able to plot these points on a graph but i don't know how to solve the problem.   make an x & y axis. ( like a cross one line goes vertical an the other horizontal) put equal dimention for x & y line From center line moving
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

how to solve for x with fractions

Simplifying x3 + 3x2 + -4x = 0 Reorder the terms: -4x + 3x2 + x3 = 0 Solving -4x + 3x2 + x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(-4 + 3x + x2) = 0 Factor a trinomial. x((-4 + -1x)(1 + -1x)) = 0 Subproblem 1 Set the factor 'x' equal to zero an
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

How do you solve this problem? solve for d: n= m+3d/4

Problem: How do you solve this problem? solve for d: n= m+3d/4 I need help solving this and seeing how it was solved since I am having trouble figuring out what to do and how to solve it thanks. n = m + 3d/4 n - m = (m + 3d/4) - m n - m = 3d/4 4(n - m) = (3d/4)4 4(n - m) = 3d 4(n - m)/3 = 3
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

Solve, using linear combination. 3x + y = 4 2x + y = 5

line 1: 3x+y=4    or y=4-3x line 2: 2x+y=5 line 1 -line2...(3x-2x)+(y-y)=4-5 or x=-1 y=4-3x=4+3=7
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

how can i solve these equations?

how can i solve these equations? x + 3y – z = 2 x – 2y + 3z = 7 x + 2y – 5z = –21 We eliminate one of the unknowns (x, y or z, take your choice), leaving two unknowns. Then, we eliminate a second one, giving us an equation with only one of the unknowns. Solve for that and plug that value in
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

Inequalities

9x+6=51 9x=51-6 9x=45 x=5
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

how do you solve 3/x+5

how do you solve 3/x+5 I'm confused on how to solve this problem All you have is an expression. There is nothing to solve until you make it an equation. 3/x + 5 = -8 3/x + 5 = 14 3/x + 5 = 0 3/x + 5 = 38.67 3/x + 5 = -91 3/x + 5 = 43 Those can be solved, because they are complete. Each one will h
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

x - z = -3, y + z = 9, -2x + 3y +5z = 33

Problem: x - z = -3, y + z = 9, -2x + 3y +5z = 33 1) x - z = -3 2) y + z = 9 3) -2x + 3y + 5z = 33 Add equation 2 to equation 1.      x     - z = -3 +(    y + z =  9) ------------------   x + y     = 6 4)
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

how to solve by substitution

how to solve by substitution .3x+3y=1.2(100) "Substitution" implies there are TWO equations in two unknowns. You solve one of them for one of the unknowns in terms of the other, e.g., solve for y in terms of x. THEN, you substitute that value into the other equation where the y is, and yo
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

2x+y=9 x-2z=-3 2y+3z=15

2x+y=9 x-2z=-3 2y+3z=15 Forgot how to do This. Problems Solving systems of this type requires eliminating all but one unknown so you can solve for that unknown. Then, plug that value into one of the equations to solve for another of the unknowns. Finally, plug both of those values into an equation
Read More: ...

Tips for a great answer:

- Provide details, support with references or personal experience .
- If you need clarification, ask it in the comment box .
- It's 100% free, no registration required.
next Question || Previos Question

Notice: Undefined variable: position5 in /home/domains2/public_html/painphr.com/show.php on line 357
  • Start your question with What, Why, How, When, etc. and end with a "?"
  • Be clear and specific
  • Use proper spelling and grammar
all rights reserved to the respective owners || www.painphr.com || Terms of Use || Contact || Privacy Policy
Load time: 0.1313 seconds